Probing Deeper Mathematical Conceptual Understanding of PISA-like Uncertainty and Data - Wahyu Widada; Khathibul Umam Zaid Nugroho; Dewi Herawaty (Journal of Mathematics Science and Education., 2025)
This study explores the effectiveness of "verbal probes" through in-depth interviews to uncover students' mathematical conceptual understandings that are not visible from written answers. Using a descriptive qualitative approach, this study analyzed the gap between written answers and verbal comprehension of three students with different skill levels on PISA-like questions themed Uncertainty and Data. The results showed a significant "gap between written answers and verbal comprehension". Students who give incorrect written answers, when interviewed, are able to articulate a deeper conceptual understanding, identify their mistakes, and explain correct procedures regarding the concepts of confidence intervals, exponential growth, and probability. In contrast, students with limited verbal comprehension consistently show reliance on number operations without a conceptual foundation. The study concludes that in-depth interviews are a crucial formative assessment tool to complement traditional methods. This allows educators to accurately diagnose misconceptions and design more holistic and targeted learning interventions.